EULAR evidence based recommendations for gout. Part II: Management. Report of a task force of the EULAR Standing Committee For International Clinical Studies Including Therapeutics (ESCISIT). Issue 10 (17th May 2006) - Zhang, W; Doherty, M; Bardin, T; Pascual, E; Barskova, V; Conaghan, P; Gerster, J; Jacobs, J; Leeb, B; Lioté, F; McCarthy, G; Netter, P; et al.
Abstract : Objective: To develop evidence based recommendations for the management of gout. Methods: The multidisciplinary guideline development group comprised 19 rheumatologists and one evidence based medicine expert representing 13 European countries. Key propositions on management were generated using a Delphi consensus approach. Research evidence was searched systematically for each proposition. Where possible, effect size (ES), number needed to treat, relative risk, odds ratio, and incremental cost-effectiveness ratio were calculated. The quality of evidence was categorised according to the level of evidence. The strength of recommendation (SOR) was assessed using the EULAR visual analogue and ordinal scales. Results: 12 key propositions were generated after three Delphi rounds. Propositions included both non-pharmacological and pharmacological treatments and addressed symptomatic control of acute gout, urate lowering therapy (ULT), and prophylaxis of acute attacks. The importance of patient education, modification of adverse lifestyle (weight loss if obese; reduced alcohol consumption; low animal purine diet) and treatment of associated comorbidity and risk factors were emphasised. Recommended drugs for acute attacks were oral non-steroidal anti-inflammatory drugs (NSAIDs), oral colchicine (ES = 0.87 (95% confidence interval, 0.25 to 1.50)), or joint aspiration and injection of corticosteroid. ULT is indicated in patients with recurrent acute attacks, arthropathy, tophi, or radiographic changes of gout. Allopurinol was confirmed as effective long term ULT (ES = 1.39 (0.78 to 2.01)). If allopurinol toxicity occurs, options include other xanthine oxidase inhibitors, allopurinol desensitisation, or a uricosuric. The uricosuric benzbromarone is more effective than allopurinol (ES = 1.50 (0.76 to 2.24)) and can be used in patients with mild to moderate renal insufficiency but may be hepatotoxic. When gout is associated with the use of diuretics, the diuretic should be stopped if possible. For prophylaxis against acute attacks, either colchicine 0.5–1 mg daily or an NSAID (with gastroprotection if indicated) are recommended. Conclusions: 12 key recommendations for management of gout were developed, using a combination of research based evidence and expert consensus. The evidence was evaluated and the SOR provided for each proposition.